„622 upadki” Witkacego w listach do żony o żonach - Narewska, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The article is a view of relation that bonds Stanislaw Ignacy Witkiewicz and Jadwiga Unrug-Witkiewicz that emerges from his mails to the wife. His view of imperfect relationship of man and woman, marriage, a relation towards the sacrament, offspring, love and faithfulness contains the traces of God’s reality.
Keywords: Stanisław Ignacy Witkiewicz; Jadwiga Unrug-Witkiewicz; Czesława Oknińska-Korzeniowska; man; woman; covenant; marriage; sacrament; offspring; faithfulnes; Decalogue; separation; abortion; repentance; faith; love; hope